Metric Distance Ranking Technique for Fuzzy Critical Path Analysis - MH Oladeinde; CA Oladeinde (Journal of Applied Sciences and Environmental Management, 2015)
In this paper, fuzzy critical path analysis of a project network is carried out. Metric distance ranking technique is used to order fuzzy numbers during the forward and backward pass computations to obtain the earliest start, earliest finish, latest start and latest finish times of the project’s activities. A numerical example is presented with a detailed step by step solution. The results of the numerical example presented are in agreement with published results in literature using other fuzzy ranking technique.© JASEM